The exploration of adolescent girl’s body composition and its relationship on hemoglobin levels in Semarang, Indonesia - Rr. Annisa Ayuningtyas; Firdananda Fikri Jauharany; Aldi Fauzi Triana (AcTion: Aceh Nutrition Journal, 2024)
The prevalence of obesity and anemia in adolescents is increasing due to an unbalanced diet and lack of physical activity. Exploration of these issues is essential for balanced nutrition education, increased physical activity, and access to nutritious foods. The study aimed to explore the relationship between body composition and hemoglobin levels among adolescent girls in Semarang City, Indonesia. The study design was cross-sectional with 110 subjects aged 14-17 years from State senior high school 2, 9, and 15 Semarang. Data were collected in September-October 2022. Waist circumferences (WC), height (H), and body fat percentage (%BF) were measured using a waist ruler, microtoise, and Bioelectrical Impedance Analyzer (BIA), respectively. Waist-to-height ratio (WHtR) is defined as waist measurement divided by height measurement in centimeters. Hemoglobin (Hb) levels were determined using point-of-care testing (POCT) methods. Data were analyzed using Rank-Spearman test and Mann-Whitney test. The results showed that among all subjects, 8,2% were anemic, 21,8% were centrally obese, and 40,9% were both obese and overweight. There is no relationship between WC (p=0,54), %BF (p=0,88), and WHtR (p=0,27) with Hb levels. Also, no difference in body composition between anemic and non-anemic adolescent girls (p>0,05). In conclusion, there are no associations between body composition and Hb levels in adolescent girls.